Red Knit Cap Girl to the rescue [book with audioplayer] - Stoop, Naoko (Findaway World, LLC, 2019)
"Red Knit Cap Girl and White Bunny, with help from Mr. Owl and the Moon, take to the high seas as they set off on a journey to help the lost Polar Bear Cub find his way back to his family and his arctic home"--